Effect of GNP and laser-surface texturing on HVOF sprayed WC10Co4Cr coatings for high-wear resistance. (February 2023) - Kumar, Vijay; Verma, Rajeev
Abstract: WC10Co4Cr and WC10Co4Cr+Graphene nano-platelets (GNPs) coatings were deposited on textured IS-2062 steel using the High Velocity Oxy-Fuel (HVOF) technique. Microhardness, wear-resistance, and bond-strength of coated specimens were investigated to assess coating soundness. In compared to WC10Co4Cr coating and pristine substrate, the microhardness of WC10Co4Cr+ 2%GNPs coating increases by 1.35 and 7.33 times, respectively. The wear-rate of WC10Co4Cr+GNPs coating decreases significantly as the percentage of GNPs increase. As WC10Co4Cr+ 4GNPs were compared to WC10Co4Cr coating and pristine substrate, the co-efficient of friction (COF) was found to be reduced by approximately 25% and 50%, respectively. Laser texturing considerably enhances the coating interface bond strength. The substantially improved performance of the WC10Co4Cr+ 2%GNPs coating could be attributed to a superior combination of microhardness and bond strength.